PTH-011 Novel Endoscopic Ultrasound-Guided Interventional Techniques for The Palliative Management of Malignant Biliary Tract Obstruction: A Single UK Centre Experience. (17th August 2016) - Paranandi, B; Oppong, KW; Rammell, J; French, JJ; Wilson, C; Dawwas, M; Nayar, MK
Abstract : Introduction: Endoscopic retrograde cholangiopancreatography (ERCP) is used as the first-line modality for biliary drainage in patients with obstructive jaundice. However, anatomical or technical factors may preclude conventional trans-papillary biliary access in less than 10% of cases. Endoscopic ultrasound-guided biliary drainage (EUS-BD) has recently emerged as an alternative method to percutaneous transhepatic biliary drainage (PTBD) or surgical biliary bypass after unsuccessful ERCP in patients with inoperable pancreatobiliary malignancies. We present initial experience of EUS-BD in our unit. Methods: A prospectively collected database, of consecutive patients undergoing EUS-BD in our unit, was analysed. Data was retrieved from electronic, clinical and endoscopy records. All EUS-BD procedures were undertaken in the endoscopy department, under conscious sedation, using Pentax echoendoscopes and Hitachi ultrasound workstations. In all cases, conventional diagnostic EUS procedure was performed followed by trans-luminal EUS-guided placement of metal stents. One of three endoscopists (KO/MN/MD) performed the procedures. The primary outcome measurements were technical success, clinical success and adverse events. Results: 4 EUS-BD procedures were performed in 4 patients – ¾ were female (75%) with median age 70 years (range 51–79). The primary indication in all patients was malignant biliary obstruction, which was not amenable to either PTBD or surgery. One patient had symptomatic cystic duct obstruction with gallbladder empyema. 1 patient received a Hot AXIOS™ covered lumen apposing metal stent (cLAMS), 1 had a Wallflex™ biliary fully covered self-expanding metal stent (fcSEMS) and the others had NAGI™ covered self-expanding metal stents (cSEMS) inserted. Technical and clinical success was 100% across all procedures with symptomatic improvement noted in all patients. Serum bilirubin measurements decremented post EUS-BD by median 89% (range 85–98%). No procedure related complications were seen. During follow up, 3/4 patients have died (median 7 months (range 3–8) from date of EUS-BD) of end-stage disease (unrelated to the EUS-BD procedure). The 4 th patient remains clinically stable on follow-up (2 months after EUS-BD) with no evidence of further biliary symptoms. Conclusion: Our early experience of EUS-BD confirms that it is a safe and effective palliative procedure in patients with malignant biliary tract obstruction, in whom surgery and/or PTBD are less favourable. We recommend that EUS-BD is performed after multidisciplinary team discussion and by experienced therapeutic endosonographers. Disclosure of Interest: None Declared